Tingkat Pengetahuan tentang Hipertensi dan Kepatuhan Minum Obat pada Lansia Penderita Hipertensi di Wilayah RT 02/RW 06 Kebagusan, Pasar Minggu - Apriyani, Elsa; Netismar, Netismar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The prevalence of hypertension among the elderly continues to increase, and the level of knowledge and medication adherence affects the success of hypertension treatment. If the elderly are non-compliant in taking their medication and lack knowledge about hypertension, they may be at risk of complications. Noncompliance with treatment, which is often caused by boredom, forgetfulness, or side effects of medication, poses a major challenge in the long-term management of hypertension. This study aims to determine the level of knowledge about hypertension and medication adherence among elderly hypertensive patients in RT 02 / RW 06 Kebagusan Pasar Minggu. This study uses a quantitative descriptive method. The study sample consists of 30 respondents selected through purposive sampling based on inclusion and exclusion criteria. Data collection was conducted using a questionnaire to assess the level of knowledge about hypertension and medication adherence for hypertension. The results showed that the majority of the elderly were aged 60–74 years (86.67%), female gender (83.33%), had a junior high school education (33.33%), had suffered from hypertension for ≥5 years (60%), had good knowledge (56.67%), and were compliant with medication (53.33%). The level of knowledge about hypertension was good, and the majority were compliant, which can help prevent complications. It is hoped that the elderly will further improve their adherence to hypertension medication as recommended by healthcare professionals.